Penguatan Budaya Sekolah dalam Membentuk Karakter Siswa Studi Kasus di SMP YPP Nurul Huda Surabaya - M Syahri SHD; M Masrur Huda; Muthoharoh, Miftakhul (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
School culture is to give direction to school members in thinking and acting, culture in this context is a series of influences on how people behave in organizations or communities, so that culture colors every aspect of social life in society when a group of people live together, then carry out activities together, the school culture in it becomes part of that life, including in a school. This thesis will focus attention on aspects of strengthening school culture in shaping student character, whether this school culture can play an important role in shaping student character, so that an effective, superior and competitive school is created so that it becomes the school of choice for the community. So is the school culture capable of strengthening the character of students? The research object is schools that are based on religion, and apply it in building student character by strengthening the school culture at SMP YPP Nurul Huda Surabaya. The method used in this study is a qualitative approach, which is a type of research that produces findings that are not obtained by means of statistical procedures or other quantification tools. This qualitative research is characterized by an emphasis on the use of non-statistics, especially in process of data analysis to produce findings naturally. The results of the study show that school culture is very effective and functions in shaping student character, which in the end the school will become superior and competitive theoretically, practically, and factually analysis. The dimensions of school culture include the dimensions of rules, behavior and norms, the philosophical dimension in the form of vision and mission and goals, and the dimensions of values. After analyzing these cultural dimensions, it shows that school culture plays a very important role and functions to strengthen students' character formation. Quality character can build a culture of achievement, so that all of these things can bring quality educational institutions as implemented at SMP YPP Nurul Huda Surabaya.